Pelatihan Kader Kesehatan Jiwa Remaja Sebagai Upaya Pencegahan Masalah Kesehatan Jiwa pada Remaja di PIK-R Kirana Kota Jambi - Nasution, Riska Amalya; Meinarisa, Meinarisa; Kamariyah, Kamariyah; Falani, Ilham (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to prevent mental health problems in adolescents by providing adolescent cadres with stress management training, recognizing mental health problems, and providing mental health cadre training to adolescents. This community service was carried out through the observation, problem formulation, preparation, implementation, and evaluation stages. The method of implementing this service used training, discussion, and simulation. The evaluation instrument used was a pre-test and post-test. Data analysis used the Wilcoxon statistical test because the data was not normally distributed. The results showed % increase in knowledge among teenage cadres who had been trained by 25%. It also showed the influence of providing youth mental health cadre training on cadre knowledge (p-value=0.000 <0.05). There was a need to strengthen knowledge through outreach activities and training for cadres who have been trained continuously.